Calculus_Refresher

Calculus_Refresher - Calculus refresher Disclaimer: I claim...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Calculus refresher Disclaimer: I claim no original content on this document, which is mostly a summary-rewrite of what any standard college calculus book offers. (Here Ive used Calculus by Dennis Zill.) I consider this as a brief refresher of the bare-bones calculus requirements we will be using during the course. No exercises are offered: any calculus book provides an insane amount of practice problems. 1. Rules of differentiation: Basics In what follows, let f ( x ) be a one-variable function, and denote its derivative by f ( x ). The standard differentiation rules are the following: Theorem 1.1 (The Power Rule, 1) . Let n be a positive integer. Then d dx [ x n ] = nx n- 1 . (1) Example 1.2. The derivative of y = x 4 is given by dy dx = 4 x 4- 1 = 4 x 3 . Theorem 1.3 (Derivative of a constant function) . If f ( x ) = k and k is a constant, then f ( x ) = 0 . Theorem 1.4 (Derivative of a constant multiple of a function) . If c is any constant and f is a differentiable function, then d dx [ cf ( x )] = cf ( x ) . (2) Example 1.5. Following theorems 1.1 and 1.4, the derivative of y = 3 x 5 is given by: dy dx = 3 d dx x 5 = 3(5 x 4 ) = 15 x 4 . Theorem 1.6 (The Sum Rule) . Let f and g be two differentiable functions. Then d dx [ f ( x ) + g ( x )] = f ( x ) + g ( x ) . (3) Example 1.7. From theorems 1.1. and 1.6, the derivative of y = x 4 + x 3 is: dy dx = d dx x 4 + d dx x 3 = 4 x 3 + 3 x 2 . Theorem 1.8 (The Product Rule) . If f and g are differentiable functions, then d dx [ f ( x ) g ( x )] = f ( x ) g ( x ) + g ( x ) f ( x ) . (4) Example 1.9. The differential of y = ( x 3- 2 x 2 + 4)(8 x 2 + 5 x ) is: dy dx = ( x 3- 2 x 2 + 4) d dx (8 x 2 + 5 x ) + (8 x 2 + 5 x ) d dx ( x 3- 2 x 2 + 4) = ( x 3- 2 x 2 + 4)(16 x + 5) + (8 x 2 + 5 x )(3 x 2- 4 x ) . Theorem 1.10 (The Quotient Rule) . If f and g are differentiable functions, then d dx " f ( x ) g ( x ) # = g ( x ) f ( x )- f ( x ) g ( x ) [ g ( x )] 2 . (5) 1 2 Example 1.11. The differential of y = 3 x 2- 1 2 x 3 +5 x 2 +7 is: dy dx = (2 x 3 + 5 x 2 + 7) d dx (3 x 2- 1)- (3 x 2- 1) d dx (2 x 3 + 5 x 2 + 7) (2 x 3 + 5 x 2 + 7) 2 = (2 x 3 + 5 x 2 + 7) (6...
View Full Document

This note was uploaded on 12/10/2010 for the course ECON 3101 taught by Professor Staff during the Spring '08 term at Minnesota.

Page1 / 5

Calculus_Refresher - Calculus refresher Disclaimer: I claim...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online